L'impact du terrorisme islamiste sur l'économie informelle africaine: le Kenya, comparé au Ghana et au Sénégal - Dirk Kohnert (Zenodo, 2022)
Sub-Saharan Africa emerged in the past years as global epicentre of Islamist terrorism. The impact of terrorism on the economy has a negative bearing on the formal and a positive effect on the informal sector. Among other things, this is due to the poorly diversified development economies of African countries and the class-specific impact of terrorism on welfare. This concerns not only a drop in sales, income and employment and rising transaction costs in the affected sectors, but also increasing poverty, hunger and hardship for the poor and needy. Transnational terrorism amplifies both the negative and the positive effects. African countries that have suffered severely from these attacks include Somalia, Kenya, Nigeria, Mali, Burkina Faso, South Sudan, Libya and Egypt. But even West African countries such as Ghana and Senegal which have been spared so far from terrorist attacks, the menace is growing, and economic effects are already tangible. Since the informal sector, i.e. the shadow economy with all its ambivalent facets, including cross-border crime, is still dominant in many African countries, especially in West Africa, this sector is of particular importance. It is still one of the largest in the world. The fight against Islamist terrorism is not just a military issue. In the economic sphere too it should be fought at its roots. Since most of the African poor live in and from the informal sector, which is also a breeding ground for criminal activities such as human trafficking of all kinds, money laundering and terrorists, they suffer the most from the negative consequences. Terrorists' sources of funding often derive from the proceeds of illegal trade. The close ties between criminal and terrorist groups can undermine the very foundations of the republican state and weaken democratic institutions – – L'Afrique subsaharienne est devenue ces dernières années l'épicentre mondial du terrorisme islamiste. L'impact du terrorisme sur l'économie a une incidence négative sur le secteur formel et un effet positif sur le secteur informel. Cela est dû, entre autres, aux économies de développement peu diversifiées des pays africains et à l'impact spécifique de classe du terrorisme sur le bien-être. Cela concerne non seulement une baisse des ventes, des revenus et de l'emploi et une augmentation des coûts de transaction dans les secteurs touchés, mais aussi une augmentation de la pauvreté, de la faim et des misères pour les pauvres et les nécessiteux. Le terrorisme transnational amplifie à la fois les effets négatifs et positifs. Les pays africains qui ont gravement souffert de ces attaques sont la Somalie, le Kenya, le Nigeria, le Mali, le Burkina Faso, le Soudan du Sud, la Libye et l'Égypte. Mais même les pays d'Afrique de l'Ouest, comme le Ghana et le Sénégal, qui ont jusqu'ici été épargnés par les attentats terroristes, la menace grandit et les effets économiques sont déjà tangibles. Étant donné que le secteur informel, c'est-à-dire l'économie souterraine avec toutes ses facettes ambivalentes, y compris la criminalité transfrontalière, est encore dominant dans de nombreux pays africains, en particulier en Afrique de l'Ouest, ce secteur revêt une importance particulière. C'est encore l'un des plus grands au monde. La lutte contre le terrorisme n'est pas seulement une question militaire. Dans le domaine économique, aussi, il faut le combattre à la racine. Étant donné que la plupart des pauvres africains vivent dans et à partir du secteur informel, qui est également un terreau fertile pour les activités criminelles telles que la traite des êtres humains de toute sortes, le blanchiment d'argent et les terroristes, ils souffrent le plus des conséquences négatives. Les sources de financement des terroristes proviennent souvent du produit du commerce illégal. Les liens étroits entre groupes criminels et terroristes peuvent saper les fondements mêmes de l'État républicain et affaiblir les institutions démocratiques.
Additional information: French version of: Kohnert, Dirk (2022): The impact of Islamist terrorism on Africa's informal economy: Kenya, compared with Ghana and Senegal
Keywords: E26; F13; F54; H56; N17; O17; P16; P26; 330; terrorisme islamist; crime organisé; État fragil; État islamique; trafic; pauvreté